Planned Shape of the CAP 2021-2027 versus Globalisation and Integration Processes - Barbara Wieliczko (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2019)
The planned CAP reform will determine the capacity of EU agriculture in facing challenges, especially those related to climate change and growing international competition. The aim of the paper is to assess the EC’s reform proposals in the context of globalisation and integration processes. The paper is based on the analysis of the EC’s proposals for the CAP 2021-2027. The results show that the proposed changes in the CAP are limited and they do not ensure significant support for the agricultural sector. They also are not adequately precise to evaluate them. Moreover, the proposed change in the CAP implementation model poses a serious risk of the CAP disintegration, which will not help the EU in its trade talks with other partners and thus can be detrimental to the future of the EU agri-food sector. It seems that the first step to make the CAP more effective is to strengthen its monitoring system.